2019
DOI: 10.3390/polym11061049
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Review of the Shape Memory Phenomena in Polymers and Their Typical Sensor Applications

Abstract: In this brief review, an introduction of the underlying mechanisms for the shape memory effect (SME) and various shape memory phenomena in polymers is presented first. After that, a summary of typical applications in sensors based on either heating or wetting activated shape recovery using largely commercial engineering polymers, which are programmed by means of in-plane pre-deformation (load applied in the length/width direction) or out-of-plane pre-deformation (load applied in the thickness direction), is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 96 publications
0
45
0
Order By: Relevance
“…A full shape memory cycle includes two steps, namely programming, which is to fix the temporary shape, and recovery, which is to apply the stimulus to active the SME. From a real engineering application point of view, such as in active disassembly [31,32], deployable structures [33] and anti-counterfeit engineering application point of view, such as in active disassembly [31,32], deployable structures [33] and anti-counterfeit applications [34][35][36][37][38][39][40], activation of the SME may not be carried out right after programming, but after a period of storage. As such, we need to consider the influence of aging at around room temperature after programming [41], which is a topic that has been less explored so far [42,43], but that is utterly important from an engineering application point of view.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A full shape memory cycle includes two steps, namely programming, which is to fix the temporary shape, and recovery, which is to apply the stimulus to active the SME. From a real engineering application point of view, such as in active disassembly [31,32], deployable structures [33] and anti-counterfeit engineering application point of view, such as in active disassembly [31,32], deployable structures [33] and anti-counterfeit applications [34][35][36][37][38][39][40], activation of the SME may not be carried out right after programming, but after a period of storage. As such, we need to consider the influence of aging at around room temperature after programming [41], which is a topic that has been less explored so far [42,43], but that is utterly important from an engineering application point of view.…”
Section: Introductionmentioning
confidence: 99%
“…It is concluded that from an engineering application point view, for this particular PMMA, programming should be done at higher temperatures (i.e., above its T g of 110 • C) in order to not only achieve reliable and better shape memory performance, but also minimize the influence of storage on the shape memory performance and mechanical behavior of the programmed material. This finding provides a useful guide for engineering applications of shape memory polymers, in particular based on the multiple-shape memory effect, temperature memory effect, and/or low temperature programming.2 of 12 applications [34][35][36][37][38][39][40], activation of the SME may not be carried out right after programming, but after a period of storage. As such, we need to consider the influence of aging at around room temperature after programming [41], which is a topic that has been less explored so far [42,43], but that is utterly important from an engineering application point of view.The purpose of this paper is to experimentally investigate the influence of storage at 40 • C on the shape memory performance and mechanical behavior of a commercial poly(methyl methacrylate) (PMMA), which is a typical engineering polymer, used in many applications, including optical lens [44,45] and plastic screw.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Shape memory polymers (SMPs) are stimuli-responsive materials. [ 1 , 2 , 3 , 4 , 5 ] Once thermomechanically treated (programmed), they maintain a temporary shape until the shape memory effect (SME) is triggered. The activation of the so-called one-way shape memory effect (1W SME) results in the almost complete recovery of the original shape.…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods would compromise the mechanical strength of the hydrogels and lead to the buckling of the film, which restricts complex and robust deformation. In practical applications of soft actuators, like artificial muscles, sensors, soft robotics, a fast response and robust deformation are both critical. Therefore, a facile and programmable method is highly desirable to create fast response/recovery actuators with a robust structure to achieve complex deformation.…”
Section: Introductionmentioning
confidence: 99%